2003
DOI: 10.1189/jlb.0202075
|View full text |Cite
|
Sign up to set email alerts
|

Cerivastatin and atorvastatin inhibit IL-3-dependent differentiation and IgE-mediated histamine release in human basophils and downmodulate expression of the basophil-activation antigen CD203c/E-NPP3

Abstract: Recent data suggest that the statins, apart from their lipid-lowering activity, exhibit profound anti-inflammatory effects. Basophils are major proinflammatory effector cells in diverse pathologic reactions. We have examined the in vitro effects of five different statins on primary human basophils, their progenitors, and the basophil cell line KU-812. Preincubation of blood basophils with cerivastatin or atorvastatin (0.1-100 microM) for 24 h reduced their capacity to release histamine on immunoglobulin E (IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Statins are cholesterol-lowering drugs that have been shown to afford protection in experimental arthritis and to decrease the disease severity in arthritic patients (Majlesi et al 2003;Barsante et al 2005;Yamagata et al 2007). In view of the pleiotropy exhibited by statins and their anti-inflammatory property, the present study was carried out to evaluate the effect of atorvastatin on the levels of oxidative stress markers in the rat model of FCA-induced monoarthritis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Statins are cholesterol-lowering drugs that have been shown to afford protection in experimental arthritis and to decrease the disease severity in arthritic patients (Majlesi et al 2003;Barsante et al 2005;Yamagata et al 2007). In view of the pleiotropy exhibited by statins and their anti-inflammatory property, the present study was carried out to evaluate the effect of atorvastatin on the levels of oxidative stress markers in the rat model of FCA-induced monoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…In both experimental and clinical studies, statins have been shown to suppress acute and chronic inflammation (Leung et al 2003;McCarey et al 2004;Van Doornum et al 2004; Barsante et al 2005;Ghaisas et al 2010). Their anti-inflammatory effect is brought about through inhibition of oedema formation, leukocyte-endothelial adhesion, and production of inflammatory mediators (Majlesi et al 2003;Yokota et al 2006). Besides, they have been shown to afford protection in various experimental models of arthritis by reducing articular inflammation, preventing bone loss and preserving bone mineral density (Yamagata et al 2007;Funk et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…In a recent report it was demonstrated that tetradecanoyl phorbol acetate (TPA), a stimulator of the protein kinase C (PKC) pathway, accelerated and enhanced CD203c upregulation, but delayed CD63 upregulation [31]. In contrast, the phosphoinositol-3 kinase (PI-3) inhibitor wortmannin effectively inhibited CD203c as well as the CD63 upregulation [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compounds having smaller structures, such as geranylacetone and farnesol, showed no effect on basophil degranulation (data not shown) . Statins inhibit intracellular geranylgeranylation, resulting in suppression of the activation profiles of inflammatory cells, [5][6][7] and basophil degranulation in response to anti-IgE antibody or PMA was significantly suppressed by preincubation with simvastatin at 50 μM (Fig. 1e).…”
mentioning
confidence: 99%
“…[5][6][7] Our present finding that exogenously added GGA can enhance basophil activation suggests that GGA enters basophils and then behaves as a substrate in the cell activation pathway. Simvastatin, which can inhibit intracellular geranylgeranylation, suppressed basophil degranulation triggered by antiIgE antibody and PMA, but not A23187.…”
mentioning
confidence: 99%